Changes of Gembili (Dioscorea esculenta) Tuber Flour Characteristics During Fermentation Process with L. plantarum B1765 Starter Culture - Prihastina, Adinda Debita; Wikandari, Prima Retno (Jurnal Pijar Mipa, 2025)
Gembili (Dioscorea esculenta) is a plant that contains inulin, which can be degraded into fructooligosaccharides known to have advantages and are widely used as food ingredients. The fermentation process can hydrolyse inulin into FOS, which is known to have better stability for food ingredients. Additionally, fermentation can produce Short-Chain Fatty Acids (SCFAs), improving consumer health and enhancing flavor, resulting in better processed products. The objective of this study was to determine changes in the characteristics of gembili tuber flour, including solubility and color, during the fermentation process, supported by data such as pH, Total Titratable Acid (TTA), and Total Lactic Acid Bacteria (TTA). Gembili tubers were cut into pieces and fermented for 0, 2, 4, and 6 days using a 3% L. plantarum B1765 starter culture and incubated at 37℃. pH measurements were taken using a pH meter, TTA using acid-base titration, total LAB using total plate count, and solubility determined by gravimetric principles. Total LAB, TTA, pH, solubility, and color were mutually correlated during the fermentation process. As more bacteria grew, pH decreased, TTA increased, solubility increased, and color became whiter. Optimal flour results were obtained at a fermentation time of 6 days, where total LAB reached 7.60 x 10⁷, pH was 3.40, TTA was 0.989%, solubility was 51.30%, and the color was the greatest white color. Fermented gembili tuber flour has more water-soluble FOS content and has better stability than inulin in non-fermented gembili flour. In addition, the colour produced from the fermentation process is also whiter than that of fermented gembili flour, which can affect the quality of the product. The FOS content in this flour can provide texture or creaminess, maintain moisture in food products, and lower the freezing point of ice cream. However, further research is still needed to determine the effect of fermentation duration on the degree of polymerisation (DP) of FOS produced during the fermentation process and the addition of fermentation time to improve the flour solubility in water.